From dangerous citizens to foreign criminals effects on human rights and state sovereignty of recent international and European responses to the terrorist threat - Sánchez-Frías, Alejandro (Revista de Estudios Europeos, 2020)
The so-called “terrorist diaspora” of Foreign Terrorist Fighters (FTFs) to their countries of residence after the defeat of Daesh is a primary concern not only for European countries, but also for the international community as a whole. Some studies have been focused on the causes of this phenomenon and its effects. However, less attention has been paid to the effects of counter terrorism measures. Since Resolution 1373, the United Nations Security Council has been developing a binding global framework against terrorism, and Resolution 2178 is the icing on this cake. This framework, accepted by many regional organizations such as the European Union and the Council of Europe, forces States to adopt measures against FTFs in areas of criminal, administrative and civil law. Firstly, these measures affect individuals because of the restrictions imposed on certain fundamental rights, such as privacy or freedom of movement. Secondly, a radical interpretation of these measures followed by its unilateral adoption can cause anarchy in the international relations between the States of origin of FTFs and the States of destination. For instance, measures preventing the movement of terrorists can be translated into the expulsion of residents or nationality deprivation, driving them to countries with less capabilities to deal with this risk. A strategy which, at the end, will increase instability in a globalised world. For these reasons, this paper proposes that the global and European frameworks against FTFs should be used as a tool to coordinate efforts, and not as a justification to defend short-term national security interests to the detriment of long-term international security.
La revista tiene una política de acceso abierto, y su web indica expresamente: "Los autores y autoras continúan como propietarios de sus trabajos, y pueden volver a publicar sus artículos en otro medio sin tener que solicitar autorización, siempre y cuando indiquen que el trabajo fue publicado originariamente en la Revista de Estudios Europeos" "Esta revista provee acceso libre inmediato a su contenido bajo el principio de hacer disponible gratuitamente la investigación al público, lo cual fomenta un mayor intercambio del conocimiento global."
Keywords: Terrorismo; United Nations; European Union; Foreign Terrorist Fighters; Revocation of Citizenship